The Effect of Using Enjoying Learning English through Edutainment to Enhance English skills for EFL learners - Linkhome, Thaweesak; Tapin, Jariyaporn (Nimitmai Review Journal, 2024)
This research aims to study the effect of using English learning through edutainment to enhance English skills for EFL learners, to improve low achievers’ English skills (listening, speaking, reading, grammar, and vocabulary), and to enhance low achievers’ positive attitudes towards English learning. This investigation was conducted using a quantitative approach. Target sampling was used to select 22 undergraduate students re-enrolled in the English Communication course in the second semester of the academic year 2022 as the study's sample size. Data analysis tools such as SPSS and t-tests were employed. The findings show that the majority of participants noted that learning English through edutainment could increase their confidence in learning English. They could learn English not only through books but also through music, animations, or movies on the Internet. They stated that they could apply the knowledge they had learned in their daily lives and their normal English classes. They opined that the class enjoyed and wanted to learn more in normal classes. The average score on the pretest was 13.91 = (1.93), whereas that on the posttest was 32.95 = (1.84). The average score of the post-test (32.95) was significantly higher than the average score of the pre-test (13.91). On average, the evaluation was satisfactory for the participants. The mean score is 3.82. The standard deviation is 0.39. According to the survey of the statements of the activities, the participants satisfied the evaluation that they were informed of the criteria before studying (the highest X-bar is 4.23), whereas the clear criteria for evaluation had the lowest average satisfaction score (X-bar = 3.86; S.D. = 0.35).